THE INFLUENCE OF DISTRICT / CITY REGIONAL CAPABILITIES AND INDEPENDENCE ON REGIONAL ECONOMIC GROWTH OF KOTA DISTRICT IN KALIMANTAN BARAT PROVINCE - B2042131026, NOVITASARI NURLAILA (Equator Journal of Management and Entrepreneurship (EJME), 2019)
ABSTRACTRegional Financial Capability and Independence is one indicator to assess the accountability of local governments in managing regional finances. This study aims to determine the influence of regency / city regional ability and independence on the economic growth of regencies / cities in West Kalimantan in the fiscal year 2009 - 2016, this study used a sample of 14 districts / cities in West Kalimantan. Analysis of research with the calculation of SPSS, ver. 24, obtained the following conclusions: a. Dependent variable (Y), Economic Growth, Independent Variable Regional Financial Capability (X1), and Regional Financial Independence (X2) .b. Normality test on N = 90 is normally distributed. c. Multicollinearity test can be seen the VIF value is 3.686, there is no multicollinearity in each variable. d. Autocorrelation Test by using DW Test or Durbin-Watson Test, autocorrelation does not occur. e. The results of Multiple Linear Regression Analysis are obtained in Equation Y = a + b (X1) + c (X2). Y = 5,102-0,226 (X1) + 0,232 (X2) is the Regional Financial Capability has an inverse relationship with the Regional Economic Growth while Regional Financial Independence has a direct relationship with regional economic growth together regional financial capability (X1) and regional financial independence ( X2) Regencies / Cities affect the Economic Growth of Regencies / Cities in West Kalimantan Province.Keywords: Ability, Independence, Growth, Economy